Activation of lignocellulosic biomass for higher sugar yields using aqueous ionic liquid at low severity process conditions. Issue 1 (December 2016) - Parthasarathi, Ramakrishnan; Sun, Jian; Dutta, Tanmoy; Sun, Ning; Pattathil, Sivakumar; Murthy Konda, N.; Peralta, Angelo; Simmons, Blake; Singh, Seema
Abstract Background Concerns around greenhouse gas emissions necessitate the development of sustainable processes for the production of chemicals, materials, and fuels from alternative renewable sources. The lignocellulosic plant cell walls are one of the most abundant sources of carbon for renewable bioenergy production. Certain ionic liquids (ILs) are very effective at disrupting the plant cell walls of lignocellulose, and generate a substrate that is effectively hydrolyzed into fermentable sugars. Conventional ILs are relatively expensive in terms of purchase price, and the most effective imidazolium-based ILs also require energy intensive processing conditions (>140 °C, 3 h) to release >90 % fermentable sugar yields after saccharification. Results We have developed a highly effective pretreatment technology utilizing the relatively inexpensive IL comprised tetrabutylammonium [TBA]+ and hydroxide [OH]− ions that generate high glucose yields ( 95 %) after pretreatment at very mild processing conditions (50 °C). The efficiency of [TBA][OH] pretreatment of lignocellulose was further studied by analyzing chemical composition, powder X-ray diffraction for cellulose structure, NMR and SEC for lignin dissolution/depolymerization, and glycome profiling for cell wall modifications. Glycome profiling experiments and computational results indicate that removal of the noncellulosic polysaccharides occurs due to the ionic mobility of [TBA][OH] and is the key factor in determining pretreatment efficiency. Process modeling and energy demand analysis suggests that this [TBA][OH] pretreatment could potentially reduce the energy required in the pretreatment unit operation by more than 75 %. Conclusions By leveraging the benefits of ILs that are effective at very mild processing conditions, such as [TBA][OH], lignocellulosic biomass can be pretreated at similar efficiency as top performing conventional ILs, such as 1-ethyl-3-methylimidazolium acetate [C2 C1 Im][OAc], but at much lower temperatures, and with less than half the IL normally required to be effective. [TBA][OH] IL is more reactive in terms of ionic mobility which extends removal of lignin and noncellulosic components of biomass at the lower temperature pretreatment. This approach to biomass pretreatment at lower temperatures could be transformative in the affordability and energy efficiency of lignocellulosic biorefineries.